Envisioning a new accountability - Lehman, Cheryl R.; Emerald eBooks (Bingley, U.K. : Emerald, 2007)
Sustainable environments, global networks, ethical financial reporting, and emancipatory accounting are increasingly shaping social and accounting dialogue. This volume contributes to a visionary accounting practice in its expansive coverage of issues and geographical perspectives prompting changes in social beliefs and levers of power.Examining these concerns with surveys and contributions from Australasia, North America, Europe, and Africa, the authors expose significant influences of the World Bank, the nature of global social investment funds, and how social responsibility is defined, perceived, and managed. Corporate and government accountability, enhancing the integrity of audited financial statements, and reforming balances of nature and power, are among the dialogue in this volume. Revealing the interconnectedness of accounting practice, corporate social responsibility, technology, the natural environment, spirituality and behavior, the authors provide new visions and potential for enhancing social policies and economic justice.
Some new evidence on the effectiveness of authoritative environmental reporting guidance / Martin Freedman, A.J. Stagliano -- Obtaining the levers of power : the treasury and the introduction of New Zealand's public sector financial reforms / Susan Newberry, Kerry Jacobs -- Corporate and government accountability for sustainable environments : the balanced scorecard approach / Fahrettin Okcabol -- Can investors detect fraud using financial statements : an exploratory study / Liming Guan, Kathleen A. Kaminski, T. Sterling Wetzel -- Gandhian-Vedic / Kala Saravanamuthu -- Interest lost : the rise and fall of a balanced scorecard project in Sri Lanka / Danture Wickramasinghe, Tharusha Gooneratne, J.A.S.K. Jayakody -- What counts in social managed investments : evidence from an international survey / Matthew Haigh -- Individual investors perceptions involving the quality and usefulness of audited financial statements / John E. McEnroe -- Social responsibility accounts : understanding world bank lending practices / Dean Neu, Elizabeth Ocampo.
Keywords: Business & Economics -- Accounting -- Governmental; Public finance accounting; Accounting; Finance; Electronic books